Outcomes of Treatment and Predictors of Response to Sofosbuvir Plus Simeprevir in Hepatitis C Virus with Genotype-4 Infection - Ahmed, Ossama A.; Elsebaey, Mohamed A; Fouad, Mohamed Hassan A.; Elkadeem, Mahmoud; Badawi, Rehab; Khayyal, Ahmed; Soliman, Shaimaa; Negm, Manal S.; Abd-Elsalam, Sherief (Infectious Disorders - Drug Targets, 2020)
Background & Aims: Treatment plan of chronic HCV infection has dramatically improved after the introduction of different groups of Direct-Acting Antiviral (DAA) drugs. These drugs have been found to be safe and effective. Sofosbuvir (SOF) plus simeprevir (SMV) regimen has been shown to be tolerable and effective in treatment of patients with HCV genotype 1. The aim of the study was to evaluate the safety and the efficacy of combined sofosbuvir plus simeprevir treatment in genotype 4 chronic HCV patients. Methods: This open-label multicenter prospective study was carried out on 381 Egyptian patients with chronic hepatitis C virus- infection. Treatment experienced and treatment-naive patients were included. Subjects administrated a regimen of sofosbuvir (400 mg/ day) plus semiprevir (150 mg /day) for twelve weeks. Sustained Virological Response (SVR) was confirmed by undetectable HCV RNA by quantitative PCR 3 months after the end of the treatment. Results: 97.6% (372 /381) of patients had SVR. None of the studied clinical and demographic characteristics were associated with the SVR status. However, patients who failed to achieve SVR showed low albumin level and high total leucocyte. The most common side effects of the studied regimen were headache, fatigue, itching, photosensitivity, and cough. Conclusions: Twelve weeks’ regimen of sofosbuvir plus simeprevir was considered to be safe and tolerable in the treatment of HCV genotype 4; also it was associated with high SVR (97.6%).
Keywords: HCV